Pemberdayaan Pemahaman Mahasiswa Melalui Perkuliahan Botani Tumbuhan Tinggi Berbasis Praktikum Lapangan - Ni Putu Yuni Astriani Dewi; Yunawati Sele (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2021)
Students' understanding of the parts of the plant body is fundamental to know as an initial step to search for plant species in nature. However, the problem faced is the lack of students' understanding of the morphological structure of plants, especially plants with high grades. Where high-class plants have a characteristic structure that is more complete and complex when compared to plants with a lower class. The method used in this research is a nature exploration method located in the Oeluan Tourism Forest, North Central Timor District, East Nusa Tenggara Province. Based on the research results, it was found that with the field practicum, students' understanding of the structure of higher plants has increased. This is shown by the assessment of the presentation posters made by each group and presented creatively which were uploaded to the YouTube application